Amagmatic hydrothermal systems on Mars from radiogenic heat - Lujendra Ojha (Nature Portfolio, 2021)
Based on the analysis of chemical maps of Thorium and Potassium derived in the Eridania region on Mars, the authors show how radiogenic heat driven hydrothermal systems may have persisted on Mars.